Financial Distress Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Martinus Robert Hutauruk; Mansyur Mansyur; Muhammad Rinaldi; Yisar Renza Situru (JPS (Jurnal Perbankan Syariah), 2021)
Companies engaged in the food and beverage business have a very high chance of success in running their business, given the increasingly high level of food and beverage consumption for the community. Information based on financial ratios needs to be improved in other forms of financial analysis to ascertain the future risk level. The purpose of this study is to analyze financial distress for food and beverage sub-sector companies listed on conventional stocks and Islamic stocks on the Indonesia Stock Exchange in the period 2015-2020. Financial distress analysis uses the Altman Z-Score bankruptcy prediction approach. The results of the study indicate that companies that experience accounting losses do not necessarily experience financial distress. Companies whose shares are listed on the Sharia stock index tend to experience healthier financial conditions and do not experience financial distress. Sharia shares of food and beverage sub-sector companies on the Indonesia Stock Exchange have good resistance to financial distress. This is supported by the high and stable value of Inti Agri Resources' shares compared to the shares of other companies.